Layout optimization and multi-scenarios for land use: An empirical study of production-living-ecological space in the Lanzhou-Xining City Cluster, China - Xuedi Yang; Xingpeng Chen; Fuwei Qiao; Lei Che; Lili Pu (Ecological Indicators, 2022)
Analysis of the dynamics of regional production-life-ecological space (PLES) can help to mitigate conflicts between economic development and the natural environment and can also promote sustainable and healthy regional development. However, the delineation and optimal integration of PLES at large scales, and predictions about its future, still lack sufficient scientific basis and reliable quantitative analysis. To fill this gap, this paper therefore chooses the city cluster as a research scale and the Lanzhou-Xining City Cluster (LXCC), an area typical of the “human-nature” conflict in northern China, as a case study. A collaborative optimal allocation of land-use (COAL) model was established to explore the future development of PLES in city clusters. In COAL, a morphological spatial pattern analysis (MSPA) and a minimum cumulative resistance model are used to determine the spatial functional areas of the country in 2020. Then, combined with the future land use simulation model, the PLES of LXCC is predicted in a multi-scenario perspective and differential control strategies are implemented for different land use functions. The results show that: (1) The identification and prioritization of source sites with important functions were the basis for enhancing the multiple functions of the land in the region. The ecological “source” of expansion accounts for 42% of the total area of LXCC, mainly in the mountains, forests, and ecological reserves, while the living “source” of expansion accounts for 58% of the total area of the city, mostly scattered on flat terrain. Based on this, five functional zones have been defined. The ecological protection zone was the largest, mainly in the western part of LXCC, and the agricultural buffer zone was the smallest. (2) The integration of different functional areas into the optimal allocation of land use is the premise of PLES delineation under the COAL framework. After a comparative analysis of multiple scenarios, the result of land use optimization under coordinated the city cluster scenario increased the area of productive land to 177,780.68 km2 and the area of living land to 13,947.33 km2. Based on this, the proportion of LXCC ecological, production, and living space were 77.20%, 18.23%, and 4.57% respectively. The optimized results have been proven to serve to meet the future spatial needs for food security and ecological conservation. The results of this study demonstrate that the COAL framework can help the government to determine the future development of PLES and promote balanced regional development in city clusters.